2019
DOI: 10.1002/ange.201901734
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting FOXP2 Oligomerization and DNA Binding

Abstract: Protein–protein and protein–substrate interactions are critical to function and often depend on factors that are difficult to disentangle. Herein, a combined biochemical and biophysical approach, based on electrically switchable DNA biochips and single‐molecule mass analysis, was used to characterize the DNA binding and protein oligomerization of the transcription factor, forkhead box protein P2 (FOXP2). FOXP2 contains domains commonly involved in nucleic‐acid binding and protein oligomerization, such as a C2H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…While a number of inferences have been made as to the purpose of the various FOXP domains through studies conducted both in vivo [5,6] and in vitro [25], the significance of the large proportion of undefined interlinking sequence in these proteins has not been considered. Bearing in mind that the undefined sequence constitutes well over 50% of the protein sequence, it is highly probable that these regions of the sequence cooperate with the defined domains so as to enable the protein to perform its function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of inferences have been made as to the purpose of the various FOXP domains through studies conducted both in vivo [5,6] and in vitro [25], the significance of the large proportion of undefined interlinking sequence in these proteins has not been considered. Bearing in mind that the undefined sequence constitutes well over 50% of the protein sequence, it is highly probable that these regions of the sequence cooperate with the defined domains so as to enable the protein to perform its function.…”
Section: Resultsmentioning
confidence: 99%
“…How exactly does such a large superfamily of ubiquitously expressed proteins have such specific non-overlapping functions, and do all parts of the sequence have a unique role to play in ensuring that the proteins perform their specific functions? While there is some evidence already available to suggest putative roles for certain parts of the sequence, (for example the polyglutamine tract and zinc finger motif are believed to be involved in protein-protein associations, the leucine zipper has been shown to cause homo and heterotypic multimerisation and the forkhead domain is responsible for DNA binding specificity [5,19,25]) it is not known how these domains, along with the remaining undefined regions of the sequence including the acid rich tail, function together to support a cohesive mechanism of transcriptional regulation. The objective of this study, therefore, is to provide more clarity on how the two oligomerisation interfaces, the leucine zipper and the forkhead domain, as well as the interlinking disordered sequence including the acid rich tail, co-operate so as to contribute to the structure and DNA binding of the FOXP proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Cooled non-reductive SDS-PAGE followed by peptide profiling supported the presence of a maturely processed low-abundance nMPO monoprotomer, Supplementary Figure S4. Single-molecule mass photometry, a method capable of quantifying the assembly, binding affinities and kinetics of protein complexes (41)(42)(43) confirmed that nMPO exists as a lowabundance monoprotomer (αβ, 7%) and highabundance diprotomer (ααββ, 93%) with an apparent mono-/diprotomer (αβ/ααββ) K d of ~50 pM, Figure 1G. The biological role(s) of the maturely processed monoprotomeric MPO, which differs from the secreted monoprotomeric proMPO reportedly elevated in blood in cardiovascular disease (44,45), remains unknown.…”
Section: Comprehensive Characterisation Of Neutrophilderived Myelopermentioning
confidence: 99%
“…Cooled non-reductive SDS-PAGE followed by peptide profiling supported the presence of a maturely processed low-abundance nMPO monomer, Supplementary Figure S4. Single-molecule mass photometry, a method capable of quantifying the assembly, binding affinities and kinetics of protein complexes (Haussermann et al, 2019;Soltermann et al, 2020;Young et al, 2018) confirmed that nMPO exists as a lowabundance monoprotomer (αβ, 7%) and high-abundance diprotomer (ααββ, 93%) with an apparent mono-/diprotomer (αβ/ααββ) Kd of ~50 pM, Figure 1G. The biological role(s) of the maturely processed monoprotomeric MPO, which differs from the secreted monoprotomeric proMPO reportedly elevated in blood in cardiovascular disease (Gorudko et al, 2018;Khalilova et al, 2018), remains unknown.…”
Section: Comprehensive Characterisation Of Neutrophil-derived Myelopementioning
confidence: 99%